Microstructure and fluid flow in the vicinity of basin bounding faults in rifts – The Dombjerg Fault, NE Greenland rift system. (December 2021) - Salomon, Eric; Rotevatn, Atle; Kristensen, Thomas Berg; Grundvåg, Sten-Andreas; Henstra, Gijs Allard
Abstract: Faults commonly form loci for high fluid flux in sedimentary basins, where fluids, rocks and deformation processes frequently interact. Here, we elucidate the interaction of fluid flow, diagenesis and deformation near basin-bounding faults in sedimentary basins through a study in the vicinity (0–3.5 km) of the Dombjerg Fault in the NE Greenland rift system. Due to fault-controlled fluid circulation, fault-proximal syn-rift clastics underwent pervasive calcite cementation, whereas uncemented clastics at some distance from the fault remained highly porous and friable. Correspondingly, two distinct deformation regimes developed to accommodate continued deformation: discrete brittle fractures formed in calcite cemented rocks, whereas cataclastic deformation bands formed in uncemented deposits. We show that low-permeable deformation bands forming in highly porous rocks were associated with localized host rock alteration, and chemical reduction of porosity along bands. In rocks with cementation-induced low porosity, brittle fractures created new pathways for fluids, but were subsequently filled with calcite. Occasionally, veins comprise multiple generations of microcrystalline calcite, likely precipitated from rapidly super-saturated fluids injected into the fractures. This suggests cemented deposits sealed uncemented compartments, where fluid overpressure developed. We conclude that compartmentalized flow regimes may form in fault-bounded basins, which has wide implications for assessments of potential carbon storage, hydrocarbon, groundwater, and geothermal sites. Highlights: Fault-controlled fluid flow leads to localized near-fault calcite cementation. Fault-related cementation compartmentalizes basin into separate deformation and flow regimes. Non-cemented clastic rock susceptible to deformation band formation and local fluid baffling. Cemented rock seals uncemented bodies and leads to fluid overpressure released during fracturing. Study showcases importance of localized cementation for fault-bounded subsurface reservoirs.